BIOTECHNOLOGY OF CULTIVATING PLANTS CONTAINING SUGAR DIABETES (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
Information is provided on medicinal plants used in diabetes mellitus, their morphophysiological properties, distribution, composition, and cultivation technology.
Keywords: Berberin, Dolchin, Onion (Trigonella foenum-graecum L.), Ginger (Zingiber offil).